2012
DOI: 10.1128/jcm.00418-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HIV-1 RNA Measurements Obtained by Using Plasma and Dried Blood Spots in the Automated Abbott Real-Time Viral Load Assay

Abstract: c Dried blood spots (DBS) may be a promising alternative specimen type to plasma for measuring the viral load (VL) in HIVinfected individuals in resource-limited settings. However, characterization of assay performance using DBS is incomplete. In this prospective study, the VL was measured in parallel using plasma and DBS specimens collected at the same time from 157 HIV-1-infected individuals. DBS were prepared by dispensing 50 l of blood onto filter paper cards and were stored desiccated at ؊20°C. Nucleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 22 publications
5
36
0
Order By: Relevance
“…Second, in order to implement the WHO recommendations of task shifting and decentralization of ART to remote settings, the consequence would be that complex procedures, including drawing blood, isolation and storage of plasma samples, and cold chain shipments to qualified labs for VL testing, should be avoided. Rather, VF should be detectable on dried blood spots (DBS), a sampling alternative that is inexpensive and easy to collect and transport and has proven application for VL testing (13,14). Third, given the fact that for accurate detection of VF, a nucleic acid amplification step remains necessary and taking into consideration the realities of contamination risks in remote labs, it was decided to concentrate on a real-time PCR approach.…”
mentioning
confidence: 99%
“…Second, in order to implement the WHO recommendations of task shifting and decentralization of ART to remote settings, the consequence would be that complex procedures, including drawing blood, isolation and storage of plasma samples, and cold chain shipments to qualified labs for VL testing, should be avoided. Rather, VF should be detectable on dried blood spots (DBS), a sampling alternative that is inexpensive and easy to collect and transport and has proven application for VL testing (13,14). Third, given the fact that for accurate detection of VF, a nucleic acid amplification step remains necessary and taking into consideration the realities of contamination risks in remote labs, it was decided to concentrate on a real-time PCR approach.…”
mentioning
confidence: 99%
“…Cell-associated residual viral replication may persist even in cART-treated patients with undetectable plasma VLs (14). In our cohort, the VLs determined from DBS may have been slightly overestimated compared to the plasma VLs, particularly in the Ͻ1,000-and 1,000-to 5,000-cp/ml groups (7). The possibility of contamination of HIV-1 DNA cannot be excluded.…”
mentioning
confidence: 61%
“…Although the accuracy of VL testing with DBS sampling may be affected by prolonged storage at high temperatures and humidity (5) and by variability in nucleic acid extraction and amplification results using commercial and in-house methods (6,9), most studies have reported high correlations between plasma viral loads and DBS results when plasma VLs exceed 5,000 HIV-1 RNA copies (cp)/ml (6,7,9,10). Wholeblood samples from DBS reflect the contribution of plasma plus cell-associated viral nucleic acids and may yield higher levels of HIV-1 RNA than those from plasma, particularly in the case of lower plasma VLs (7,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Where DBS have been trialed as an alternative sample for VL monitoring, it was suspected that proviral DNA was being coamplified with viral particle RNA. One study on the feasibility of using DBS with the Abbott RealTime VL assay found that in 9% of samples with a plasma VL of Ͻ40 copies/ml, the corresponding DBS sample had a detectable nucleic acid content (17). Furthermore, this study demonstrated with a specific RT reaction that these DBS samples had undetectable RNA levels, strongly suggesting that proviral DNA was the source of reactivity.…”
Section: Discussionmentioning
confidence: 87%